Retrospective Analysis of Atypical Glands Suspicious for Carcinoma in Transurethral Resection of Prostate. Issue 3 (March 2018) - Chen, Sonja; Patil, Pallavi A.; Lepe, Marcos; Lombardo, Kara A.; Amin, Ali; Matoso, Andres
Abstract : Prostate biopsies with foci of atypical glands suspicious, but not diagnostic of carcinoma (ATYP) are associated with an increased risk of cancer diagnosis in subsequent biopsies. The significance of similar findings in transurethral resections of the prostate (TURP) is unknown. A total of 1338 specimens without a diagnosis of cancer were retrieved from our surgical pathology files from 1994 through 2014. Of these, 18 cases (1.3%) were identified with the diagnosis of ATYP. Immunohistochemistry (IHC) for p63, high molecular weight cytokeratin, and racemase (PIN4) was performed in all cases. The cases were grouped based on the main benign mimicker of cancer that could not be excluded from the differential diagnosis and prevented a definitive diagnosis. Adenosis accounted for 50% of the cases (9/18), 33.3% of the cases (6/18) were cautery artifact, 11% of the cases (2/18) were basal-cell hyperplasia with nucleoli and 5.6%, a single case, cribriform clear cell hyperplasia could not be excluded. Eight patients had follow-up biopsies and 2 were diagnosed with prostatic adenocarcinoma Gleason grade 3+3=6; both were alive 3 years after initial diagnosis. Although the most frequent benign mimickers that prevent a definitive diagnosis of cancer in needle biopsies are the small size of the atypical foci, PIN and partial atrophy, in TURPs, they are adenosis and cautery artifact. The rate of cancer diagnosed in follow-up is similar or lower than in patients with prior benign prostate needle biopsies and significantly lower than in patients with a prior diagnosis of ATYP in biopsies of the peripheral zone.